乡土·生态：《山南水北》中的“复魅”书写 = Soil and ecology: the “re-enchantment” in the writing of Shan Nan Shui Bei - 陈秋静 Chen, Qiujing (Nanyang Technological University, 2025)
二十世纪以来，中国步入工业化进程，经济建设也逐渐变成国家发展的核心目标。然而在快速发展的同时，自然资源遭到过度开采，从而导致森林砍伐、土壤侵蚀、水资源浪费等环境问题。这些问题由于在当时并未得到足够重视，因此随着城市化、现代化的激进推进反而愈演愈烈。在这样的背景下，乡村成为了首当其冲的受害者，进而成为了许多作家笔下的书写对象。当代中国重要作家之一韩少功亦不例外，他在跨文体长篇作品《山南水北》中，展现了工业化和城市化对乡村生态的冲击，同时也彰显了其生态意识与乡土情怀。 本文首先回顾“乡土文学”和“生态文学”的概念，并对二者结合而产生的“乡土生态文学”进行阐释。之后，再对“乡土生态文学”与《山南水北》之间的内在关系展开讨论。其次，本文将界定“魅”的概念，并对马克斯·韦伯的“祛魅”理论与大卫·雷·格里芬的“复魅”理论进行阐释。之后，本文以格里芬的理论为基础，对《山南水北》的“复魅”美学展开分析。最终，本文得出结论：《山南水北》是乡土文学与生态文学的融合下，运用“复魅”美学构建独特的生态叙事与文化反思的作品。其不仅拓展了生态文学的表达维度，也为当代文学提供了新的思考路径。 Since the 20th century, China has embarked on a process of industrialization, with economic development gradually becoming the central focus of national progress. However, rapid growth has come at the cost of excessive resource exploitation, leading to environmental issues such as deforestation, soil erosion, and water resource depletion. These problems were not sufficiently addressed at the time. As urbanization and modernization advanced aggressively, the problems became increasingly severe. Under this context, rural areas bore the brunt of the impact and became a focal point in the writings of many authors. Han Shaogong, one of the most significant contemporary Chinese writers, is no exception. In his cross-genre novel Shan Nan Shui Bei, he not only depicts the impact of industrialization and urbanization on rural areas but also conveys his ecological consciousness and deep affection for rural life. This paper first reviews the concepts of “Native Soil Literature” and “Ecological Literature”, as well as elaborates on the fusion of these two into “Native Ecological Literature”. Then, the paper will explore the relationship between this new genre and Shan Nan Shui Bei. Secondly, the paper defines the concept of “enchantment” and discusses Max Weber’s theory of “disenchantment” and David Ray Griffin’s theory of “re-enchantment”. Based on Griffin’s theory, this paper then analyzes the aesthetics of “re-enchantment” in Shan Nan Shui Bei. Finally, the paper concludes that Shan Nan Shui Bei is a work that integrates native soil literature and ecological literature, employing the aesthetics of “re-enchantment” to construct a unique ecological narrative and cultural reflection. Not only does it expand the expressive dimensions of ecological literature, but it also offers new perspectives for contemporary literary studies.